2007
DOI: 10.1111/j.1551-2916.2007.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

TEM/STEM Observation of ZrC‐Coating Layer for Advanced High‐Temperature Gas‐Cooled Reactor Fuel

Abstract: The Japan Atomic Energy Agency (JAEA) has started to study and develop ZrC‐coated fuel particles for advanced high‐temperature gas‐cooled reactors. The ZrC‐coating layer was fabricated using the bromide process at JAEA. In the early stage of the project, however, the deposition temperature was varied. This paper mainly focuses on the microstructures of the ZrC‐coating layer developed in the early stage of the project. Some circumferential stripes were observed in the ZrC‐coating layer on optical micrographs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 8 publications
1
21
4
Order By: Relevance
“…These appeared to be lattice fringes, similar to the free carbon region observed in the ZrC layer of the ZrC‐05‐2003 batch, 6 in the above‐mentioned laminar features when observed with a high‐resolution TEM. It is therefore reasonable to assume that these laminar features consisted of mainly free carbon 6 . The free carbon regions were distributed in the ZrC layer uniformly (in micrometer order) and quite densely (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…These appeared to be lattice fringes, similar to the free carbon region observed in the ZrC layer of the ZrC‐05‐2003 batch, 6 in the above‐mentioned laminar features when observed with a high‐resolution TEM. It is therefore reasonable to assume that these laminar features consisted of mainly free carbon 6 . The free carbon regions were distributed in the ZrC layer uniformly (in micrometer order) and quite densely (Fig.…”
Section: Resultssupporting
confidence: 57%
“…We have reported some characteristics of the microstructures of the ZrC layer produced in an early stage of the project (batch number: ZrC‐05‐2003) 6 . The deposition temperature for the ZrC‐05‐2003 batch was not constant but oscillated in a temperature range of 1493–1823 K 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dark contrast areas seen in the ZrC layers correspond to voids or free carbons region. 11) Before the heat treatment, the voids or free carbons region had a thin ($10 nm) layered feature and were distributed densely (some 10 nano-meters interval) 9) (see Fig. 1(a)).…”
Section: Methodsmentioning
confidence: 99%
“…5 [11]. From this figure, it was indicated that the high-dense regions designated as (b) and the low-dense regions as (a) were layered with a relation to the deposition direction.…”
Section: Microstructure Of the Obtained Zrc Coating Layermentioning
confidence: 97%